Late preterm births: a retrospective analysis of the morbidity risk stratified for gestational age - Marrocchella, Sonia (Springerplus, 2014)
PURPOSE: Late-preterm births are considered functionally mature but, several line of evidences suggest that, compared with term neonates, they have a higher risk of complications. The aim of this study was to compare the incidence of maior clinical complications of late preterm infants born in our division, compared to those born at term. METHODS: We retrospectively analysed late preterm deliveries occurred in a twenty-months period. Late preterms were divided in 3 sub-groups according to gestational age at delivery: 34 0/6 , 35 0/6 , 36 0/6 weeks of gestation. The incidence of maior clinical complications was evaluated. Statistical analysis was performed by using the Z- test. RESULTS: Among term deliveries 17.24% were admitted to the neonatal intensive care unit and 69.01% presented one major adverse outcome: 25.35% jaundice, 25.35% hypoglycemia , 11.26% RDS , 4.22% intraventricular hemorrhage (IVH), 4,22% anemia. The incidence of IVH was significantly higher only at 340/6 weeks of gestation compared to term infants. The incidence of anemia and RDS was significantly higher at 34 0/6 and 35 0/6 weeks of gestation, but it was not significantly different at 36 weeks of gestation, compared to full-term infants. Finally, the incidence of hypoglycemia and jaundice results significantly higher in all the 3 sub groups of late preterms, compared to full term infants. CONCLUSIONS: Results demostrated an increased risk of morbidity in the late preterm period. Results also showed that the gestational age at delivery of late preterms can influence the risk of adverse neonatal outcomes.